Estudio de prefactibilidad para la elaboración de una bebida energética a base mate de hoja de coca (Erythroxylum coca) y kiwicha (Amaranthus caudatus) con saborizantes naturales en Lima Metropolitana - Baca Montoya, Sebastian Elias (2023)
The purpose of the present investigation is demostrate the technical, economic, social and market feasibility regarding the implementation of a manufacturing plant for energy drinks naturally prepared with kiwicha (Amaranthus caudatus) and coca leaf mate (Erythroxylum coca), materials from the region of Peru, with natural flavors in Lima Metropolitana. This product is considered a healthy product, due to the beneficial properties of raw materials, the low content of additives and chemicals and the low content of caffeine. In addition, the packaging shall have a capacity of 300ml. The project’s objective market will be people, men and women, from ages 16 to 65 years from Metropolitan Lima, mainly those belonging to socioeconomic status A, B and C1, which will get the product from modern and traditional channels like supermarkets, modern markets, hypermarkets, among others. Using the results of the application of a survey, secondary information and projection techniques, it was estimated that a demand of 135 297 litres of energy drink for the year 2020, the first year of the project, and 196 058 litres by the year 2024, last year of the project. The production plant will take place at the Macropolis project, the largest industrial city in all of Peru, in Lurín, due to easy access to transport, installation costs, water supply, excellent sanitation services and waste disposal. This decision was reached through the factor ranking analysis for macro and micro localization and secondary information. Also, to determine the size of the plant, several limiting factors were considered, which are: market, productive resources, technology and the breakeven point. In this way, it was obtained that the market size is the limiting with 653 525 units / year. We performed the analysis about the engineering required by the project, resulting in the technical definitions of the product, necessary technologies, production capabilities, services and methods of assuring the quality, occupational safety and health, environmental impacts, maintenance management for technologies, suply chain, and production schedules. In addition, it was determined that 13 administrative staff and 8 operators will be required for a production plant of 360 m². Finally, the economic, financial and social viability of the pre-feasibility study was determined. To this end, investments, revenues, expenses and production costs were for budgeted for the purpose of preparing the financial. In economic terms, after financial analysis, it was obtained that the required investment is S/1 495 450, 44% of it will be financed by an external entity, the difference being own investment. In addition, the financial evaluation for the next five years resulted in a FNPV of S/1 890 145; a FIRR of 89% and a benefit-cost (B/C) of 2,25; proving the Project profitability. On the other hand, the economic evaluation obtained a ENPV of S/1 761 970, an EIRR of 63% and a benefit-cost ratio (B/C) of 1,27. Finally, it was obtained that the accumulated added value at the end of the project would be S/6 944 403.